GREEN ACCOUNTING STUDY IN RETAIL COMPANIES: A REVIEW OF ENVIRONMENTAL ETHICS IN SYMBOLIC DISCLOSURE - saadah, naili saadah (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2024)
Environmental problems are currently a problem that is often studied in various parts of the world, including in Indonesia, the environment begins to be noticed when humans have felt the impact of environmental damage. Especially if it is associated with industrial waste considering the impact of industrial waste caused by poor environmental management. The issue of environmental damage, its causes and impacts on human life in the present as well as future impacts cause the entire community to realize the importance of preserving the environment. Many countries around the world have mandated companies to establish green accounting and to disclose environmental information for the reference of interested parties. However, because the disclosure of environmental responsibility is not as clearly implied as SAK, in its implementation many entities do not explain in detail so that they seem to be only uncles.As an effort to uncover the implementation of environmental concerns carried out by the company, this research is here to explore more deeply by comparing what has been written in the report with real implementation. Is it just fulfilling the legitimacy of society or is there a growing awareness of environmental concerns.Using the quality method with content analysis techniques for annual report reports and in-depth interviews to find out the direct implementation related to green accounting in retail companies, the results of the study prove that of the four business entities engaged in retail, only one entity is already concerned related to environmental improvement and is reflected in the vision and mission and direct policies, Meanwhile, one more entity has shown the seriousness of efforts to improve the environment and one entity even though it has implemented a plastic bag restriction policy but still as an effort to fulfill the responsibilities given by the government